Cellulose composite carbon aerogel, preparation method thereof and application of cellulose composite carbon aerogel in aspect of battery electrode
By combining cellulose nanofibers with carbon nanotubes, a cellulose composite carbon aerogel was prepared, which solved the problem of insufficient compressibility and mechanical strength in cellulose carbon aerogel in battery electrode applications, and achieved the effects of high specific surface area, excellent compression and electrochemical activity.
Patent Information
- Application Number
- CN202411770963.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
Existing cellulose carbon aerogels have problems with poor compressibility and mechanical strength in battery electrode applications.
Cellulose composite carbon aerogel is prepared by mixing cellulose nanofibers and carbon nanotubes as raw materials, and mixing dispersions, bidirectional freezing, freeze-drying and high-temperature carbonization.
The cellulose composite carbon aerogel prepared by this method has an ultra-large specific surface area and excellent compression rate at ultra-low density, showing ultra-hydrophilicity and high electrochemical activity, good compression elasticity, good structural stability and certain mechanical strength, and is suitable for liquid flow battery electrodes.
Smart Images

Figure BDA0005170263220000041 
Figure BDA0005170263220000071 
Figure BDA0005170263220000072
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a cellulose composite carbon aerogel and a preparation method thereof and application in battery electrodes. Background Art
[0002] Liquid flow battery is a new type of battery. It is a high-performance battery that uses positive and negative electrolytes to circulate separately. It is a new energy product. Liquid flow battery has the advantages of long cycle life, high safety, green environmental protection, and decoupling of power and capacity. As one of the preferred technologies for large-scale long-term energy storage, it can achieve smooth output of renewable energy and provide guarantee for the grid-connected application of high proportion of renewable energy.
[0003] As a multifunctional key component in the liquid flow battery system, the electrode is a platform for the electrochemical reaction of the active substances in the electrolyte. The performance of the electrode determines the polarization degree of the electrochemical / ohmic / concentration difference of the liquid flow battery, and directly affects the coulombic efficiency and current density of the battery. The electrode material should have a high specific surface area, electrochemical activity, high effective porosity, good conductivity, strong acid and alkali resistance, and strong redox properties. At present, carbon electrodes are commonly used in liquid flow battery electrodes. Carbon electrodes generally use materials such as carbon felt, graphite felt and carbon cloth. They have the characteristics of good conductivity, corrosion resistance and stable chemical properties. However, their electrochemical activity and hydrophilicity are poor.
[0004] Carbon aerogel has low density, high porosity, high specific surface area, super hydrophilicity and excellent conductivity, and is one of the ideal materials to solve the defects of carbon electrodes. Cellulose nanofibers and their derivatives can be constructed into nanocellulose carbon aerogels with a three-dimensional network structure. Their unique three-dimensional network structure and large specific surface area can be used as carbon skeleton support materials or carbon matrix materials for conversion and energy storage. Therefore, the application of cellulose carbon aerogel to the electrode part of liquid flow batteries has good development prospects. However, cellulose carbon aerogel has certain disadvantages in compressibility and mechanical strength when used as an electrode, which limits the application of cellulose carbon aerogel in electrodes. The above problems need to be solved urgently. Summary of the invention
[0005] In order to solve the above technical problems, the technical solution adopted in this application is to provide a cellulose composite carbon aerogel and its preparation method and application in battery electrodes, so as to solve the technical problems of poor compressibility and mechanical strength of existing cellulose carbon aerogels.
[0006] A first aspect of an embodiment of the present application provides a method for preparing a cellulose composite carbon aerogel, comprising the following steps:
[0007] (1) preparing a suspension: mixing cellulose nanofibers, 2,2,6,6-tetramethylpiperidin-1-oxyl free radicals and sodium bromide in deionized water, stirring evenly, and adding sodium hydroxide to adjust the pH to about 10; adding sodium hypochlorite while stirring at room temperature, and continuously adding sodium hydroxide to keep the pH at about 10.5 until the pH value no longer decreases, and then adding ethanol to terminate the reaction; washing the product with deionized water until it is neutral, preparing a slurry, centrifuging, obtaining a cellulose nanofiber suspension, and refrigerating;
[0008] (2) Mixing and dispersion: adding the refrigerated cellulose nanofiber suspension to the carbon nanotubes, vigorously stirring and ultrasonically dispersing to obtain a mixed solution, which is then refrigerated;
[0009] (3) Bidirectional freezing: The mixed liquid is poured into a polytetrafluoroethylene mold. The bottom of the mold is connected to a copper column placed in liquid nitrogen. The temperature is transferred upward along the copper column, and the mixed liquid is gradually frozen.
[0010] (4) Freeze drying: freeze drying the completely frozen mixed solution to obtain cellulose nanofiber / carbon nanotube composite aerogel;
[0011] (5) High temperature carbonization: The cellulose nanofiber / carbon nanotube composite aerogel is subjected to high temperature pyrolysis to obtain a cellulose nanofiber / carbon nanotube composite carbon aerogel, namely, a cellulose composite carbon aerogel.
[0012] Preferably, in step (1), the molar ratio of cellulose nanofibers, 2,2,6,6-tetramethylpiperidin-1-oxyl free radical, sodium bromide and sodium hypochlorite is 8-9:1:1:1-2.
[0013] Preferably, in step (1), the concentration of the slurry is 2 mg / mL; the slurry is centrifuged at 800-1200 r / min for 10-20 min; and the slurry is refrigerated at 4°C.
[0014] Preferably, in step (2), the mass ratio of cellulose nanofibers to carbon nanotubes is 1:0.5-2; and the vigorous stirring time is 20-40 min.
[0015] Preferably, in step (2), the mixture is refrigerated at 4°C.
[0016] Preferably, in step (3), the temperature of liquid nitrogen is -65--55°C, and the freezing time is 8-12h.
[0017] Preferably, in step (4), freeze drying is performed at -60--50°C for 70-74h.
[0018] Preferably, in step (5), pyrolysis is performed at 700-900° C. for 0.5-2 h.
[0019] A second aspect of the embodiments of the present application provides a cellulose composite carbon aerogel prepared by any of the preparation methods described above.
[0020] A third aspect of the embodiments of the present application provides an application of a cellulose composite carbon aerogel prepared by any of the preparation methods described above in battery electrodes.
[0021] The present invention provides a cellulose composite carbon aerogel and a preparation method thereof, wherein cellulose nanofibers (CNFs) and carbon nanotubes (CNTs) are used as raw materials, and after dispersion mixing and dispersion, cellulose nanofibers / carbon nanotubes composite carbon aerogel (CNFs / CNTs composite carbon aerogel) is prepared by bidirectional freezing, freeze drying, and high-temperature carbonization, namely, cellulose composite carbon aerogel. The present invention also provides the application of cellulose composite carbon aerogel in battery electrodes, which has a large specific surface area and excellent compression rate at ultra-low density, exhibits superhydrophilicity and high electrochemical activity, good compression resilience, good structural stability and certain mechanical strength, and can be used in various electrochemical-based water-based liquid flow batteries.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) Individual CNFs fibrils are cross-linked within the layer. Although aerogels can be constructed, only some of the fibrils between the layers play a supporting and connecting role, resulting in smaller pores in the aerogel and unclear boundaries between the layers. After adding CNTs, since CNTs and CNFs are not only cross-linked within the layer but also between the layers, CNTs play a supporting and connecting role, forming an aerogel with a honeycomb structure, making the pore structure more developed and less prone to collapse, and at the same time, the thermal degradation rate is lower. Under the same high-temperature carbonization conditions, its microstructure is more stable and the degree of graphitization is higher. Therefore, CNFs / CNTs is used as a precursor of carbon aerogel, making the CNFs / CNTs composite carbon aerogel have good structural stability and mechanical strength.
[0024] (2) The honeycomb structure of CNFs / CNTs composite carbon aerogel enables it to effectively transmit compressive stress, withstand large compressive strain, and have good compressibility and elasticity. At the same time, the addition of CNTs significantly improves the structural stability of CNFs / CNTs composite carbon aerogel. The two work synergistically to improve the compressibility and elasticity of CNFs / CNTs composite carbon aerogel and ensure its mechanical strength.
[0025] (3) The porous structure and high surface roughness of CNFs make CNFs / CNTs composite carbon aerogel have ultra-low density, super hydrophilicity and high electrochemical activity. The ultra-low density can reduce the weight of the flow battery assembly design. The super hydrophilicity and high electrochemical activity can effectively reduce the resistance of electrolyte transmission during the operation of the flow battery, improve the wettability, transmission rate and mass transfer uniformity of the electrolyte, thereby effectively reducing the polarization phenomenon and improving the utilization rate of the electrolyte. DETAILED DESCRIPTION
[0026] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0027] The present invention provides a cellulose composite carbon aerogel and a preparation method thereof and application in battery electrodes. The raw materials and equipment used are conventional commercially available products, and their specific sources are shown in Table 1.
[0028] Table 1 Sources of raw materials
[0029]
[0030] In order to verify the reliability of the present invention and its effects, the present invention is described below in conjunction with Examples 1-11 and compared with Comparative Examples 1-2.
[0031] (I) Cellulose composite carbon aerogel and its preparation method
[0032] Example 1
[0033] A method for preparing a cellulose composite carbon aerogel comprises the following steps:
[0034] (1) Preparation of suspension
[0035] CNFs, TEMPO and NaBr were added to deionized water in a molar ratio of 8:1:1, mixed and stirred until uniform, and then 0.5 mol / L NaOH solution was added to adjust the pH to about 10; then, 10% NaClO was added at room temperature while stirring, and the molar ratio of TEMPO to NaClO was 1:1 to start the oxidation process of CNFs, and 0.5 mol / L NaOH solution was continuously added to keep the pH of the system at about 10.5 until the pH value no longer decreased, and then a large amount of ethanol was added to terminate the reaction;
[0036] The obtained reaction product was thoroughly washed with deionized water several times until it was neutral, and then prepared into a 2 mg / mL slurry, centrifuged at 1000 r / min for 15 min using a centrifuge to obtain a CNFs suspension, which was refrigerated at 4°C.
[0037] (2) Mixing and dispersion
[0038] The refrigerated CNFs suspension was added to CNTs, with the mass ratio of CNFs suspension to CNTs being 1:1. After vigorous stirring for 30 min, ultrasonic dispersion was performed to obtain a mixed solution after uniform dispersion, which was refrigerated at 4°C.
[0039] (3) Two-way freezing
[0040] The refrigerated mixed liquid is poured into a square polytetrafluoroethylene mold. The bottom of the mold is connected to a copper column placed in liquid nitrogen at -60°C. The temperature is transferred upward along the copper column, and the mixed liquid is gradually frozen. The freezing time is 10 hours.
[0041] (4) Freeze drying
[0042] The completely frozen mixed solution was freeze-dried in a freeze dryer at -56°C for 72 h to obtain CNF / CNT composite aerogel.
[0043] (5) High temperature carbonization
[0044] The CNF / CNT composite aerogel was subjected to high temperature pyrolysis at 800°C for 1 h in a tubular furnace under a N2 atmosphere and then cooled to room temperature to obtain a CNFs / CNTs composite carbon aerogel, namely a cellulose composite carbon aerogel.
[0045] Example 2
[0046] The difference between this embodiment and Example 1 is that in step (1), the molar ratio of CNFs, TEMPO and NaBr is 8.5:1:1, and the remaining operations are the same to obtain CNFs / CNTs composite carbon aerogel.
[0047] Example 3
[0048] The difference between this embodiment and Example 1 is that in step (1), the molar ratio of CNFs, TEMPO and NaBr is 9:1:1, and the remaining operations are the same to obtain CNFs / CNTs composite carbon aerogel.
[0049] Example 4
[0050] The difference between this embodiment and Example 1 is that in step (1), the molar ratio of TEMPO to NaClO is 1:1.5, and the remaining operations are the same to obtain CNFs / CNTs composite carbon aerogel.
[0051] Example 5
[0052] The difference between this embodiment and Example 1 is that in step (1), the molar ratio of TEMPO to NaClO is 1:2, and the remaining operations are the same to obtain CNFs / CNTs composite carbon aerogel.
[0053] Example 6
[0054] The difference between this embodiment and Example 1 is that in step (2), the mass ratio of CNFs suspension to CNTs is 1:0.5, and the remaining operations are the same to obtain CNFs / CNTs composite carbon aerogel.
[0055] Example 7
[0056] The difference between this embodiment and Example 1 is that in step (2), the mass ratio of CNFs suspension to CNTs is 1:2, and the remaining operations are the same to obtain CNFs / CNTs composite carbon aerogel.
[0057] Example 8
[0058] The difference between this embodiment and Example 1 is that in step (5), pyrolysis is performed at 700° C., and the remaining operations are the same to obtain CNFs / CNTs composite carbon aerogel.
[0059] Example 9
[0060] The difference between this embodiment and Example 1 is that in step (5), pyrolysis is performed at 900° C., and the remaining operations are the same to obtain CNFs / CNTs composite carbon aerogel.
[0061] Example 10
[0062] The difference between this embodiment and Example 1 is that in step (5), the pyrolysis is carried out for 0.5 h, and the remaining operations are the same to obtain CNFs / CNTs composite carbon aerogel.
[0063] Embodiment 11
[0064] The difference between this embodiment and Example 1 is that in step (5), pyrolysis is performed for 2 h, and the remaining operations are the same to obtain CNFs / CNTs composite carbon aerogel.
[0065] It should be noted that: in the above-mentioned embodiments 1-11, in step (1), the slurry concentration is 2 mg / mL, the centrifugal rate is 1000 r / min, and the centrifugal time is 15 min. This is only a preferred embodiment. In actual production, the centrifugal rate can be 800-1200 r / min, and the centrifugal time can be 10-20 min. The slurry concentration, centrifugal rate, and centrifugal time can all be adaptively adjusted according to specific circumstances. In steps (1) and (2), the temperature of the cold storage treatment is 4 ° C. This is only a preferred embodiment. In actual production, the temperature of the cold storage treatment can be adaptively adjusted according to specific circumstances. In step (2), the time of vigorous stirring is 30 min. This is only a preferred embodiment. In actual production, the time of vigorous stirring can be 20-40 min. In actual operation, it is adaptively adjusted according to specific circumstances. In step (3), the liquid nitrogen temperature is -60°C and the freezing time is 10 hours. This is only a preferred embodiment. In actual production, the liquid nitrogen temperature can be -65--55°C and the freezing time can be 8-12 hours. In actual operation, adaptive adjustment is performed according to specific circumstances. In step (4), the freeze-drying temperature is -56°C and the freeze-drying time is 72 hours. This is only a preferred embodiment. In actual production, the freeze-drying temperature can be -60--50°C and the freeze-drying time can be 70-74 hours. In actual operation, adaptive adjustment is performed according to specific circumstances.
[0066] In order to more intuitively compare the preparation process parameters of the CNFs / CNTs composite carbon aerogels of Examples 1-11, the following Table 2 is formed.
[0067] Table 2 Preparation process parameters of CNFs / CNTs composite carbon aerogels of Examples 1-11
[0068]
[0069]
[0070] (II) Application of cellulose composite carbon aerogel in battery electrodes
[0071] (1) Used as an electrode
[0072] The CNFs / CNTs composite carbon aerogel prepared in Example 1-11 was cut into rectangles of 5 mm×5 mm×2.5-4 mm, which were CNFs / CNTs composite carbon aerogel electrodes.
[0073] Comparative Example 1: A commercially available graphite felt electrode, produced by Liaoning Jingu Carbon Material Co., Ltd., batch number 442638055-2, mainly composed of graphite felt, was cut into the same size as the CNFs / CNTs composite carbon aerogel electrode.
[0074] The performance of the CNFs / CNTs composite carbon aerogel electrodes of Examples 1-11 and the commercially available graphite felt electrodes of Comparative Example 1 were tested in accordance with the provisions of NB / T42082-2016 "Test Methods for Electrodes of All-Vanadium Redox Flow Batteries". 2 , current density 160ma / cm 2 , pump speed 100mL / min.
[0075] The test results are shown in Table 3.
[0076] Table 3 Technical indicators of electrodes
[0077]
[0078]
[0079] From Table 3 we can see that:
[0080] Compared with commercially available graphite felt electrodes, the CNFs / CNTs composite carbon aerogel electrode prepared in Example 6 has the best performance. This is because under the same preparation conditions, when the addition of CNTs is relatively low, sufficient structural stability and mechanical strength are obtained by providing the most basic aerogel support connection, and the honeycomb pore structure of the cellulose aerogel can be retained to the maximum extent, thereby retaining a larger specific surface area, compressibility and electrochemical activity.
[0081] On the contrary, the overall performance of the CNFs / CNTs composite carbon aerogel electrode prepared in Example 7 is slightly low. Example 8 is not friendly to the structure of cellulose aerogel due to the low pyrolysis temperature and Example 10 due to the short pyrolysis time. The lower pyrolysis temperature and shorter pyrolysis time are not conducive to the introduction of oxygen-containing functional groups and structural stability. Example 9 is not conducive to the stability of the aerogel crystal structure due to the high pyrolysis temperature. TEMPO and NaClO in this application are catalysts and oxidants, respectively, where TEMPO can increase the hydrophilicity and reactivity of cellulose to form super-hydrophilicity, and NaClO acts as an oxidant to promote the oxidation of primary alcohol hydroxyl groups in cellulose to generate carboxyl groups; however, due to the high content of NaClO in Example 5, excessive degradation of cellulose may occur, affecting the mechanical properties and stability of the aerogel.
[0082] (2) Used as a battery stack
[0083] The CNFs / CNTs composite carbon aerogel prepared in Example 1-11 was cut into rectangles of 5 mm×5 mm×2.5-4 mm, and 5 pieces were used together to form a CNFs / CNTs composite carbon aerogel stack.
[0084] Comparative Example 2: The commercially available graphite felt electrode of Comparative Example 1 was cut into the same size as the CNFs / CNTs composite carbon aerogel electrode, and 5 pieces were used together to obtain a commercially available graphite felt stack.
[0085] The performance of the CNFs / CNTs composite carbon aerogel stacks of Examples 1-11 and the commercially available graphite felt stack of Comparative Example 2 were tested below. The test method was carried out in accordance with the provisions of NB / T42137-2017 "Test Method for All-Vanadium Redox Flow Battery Stacks".
[0086] The test results are shown in Table 4.
[0087] Table 4 Technical indicators of the battery stack
[0088]
[0089] From Table 4 we can see that:
[0090] Compared with the commercially available graphite felt stack, the performance of the CNFs / CNTs composite carbon aerogel stack prepared in Example 6 is the best. On the contrary, the overall performance of the CNFs / CNTs composite carbon aerogel stack prepared in Examples 1-5 and 7-10 is slightly lower, but all are better than the performance of the commercially available graphite felt stack. The above results are consistent with the results used as electrodes in Table 3.
[0091] As shown in Table 3 and Table 4, compared with the commercially available graphite felt electrode / electric stack, the CNFs / CNTs composite carbon aerogel prepared in Examples 1-11 of the present invention has a large specific surface area and excellent compression rate at ultra-low density, its own super hydrophilicity and high electrochemical activity, good compression resilience, good structural stability and certain mechanical strength, which makes it have a unique advantage in the use of liquid flow battery electrodes. This is determined by the preparation method of the present invention.
[0092] The CNFs / CNTs composite carbon aerogel of the present invention solves a series of defects of traditional electrodes by virtue of its superior honeycomb network structure, ultra-high hydrophilicity and certain mechanical strength, improves the electrochemical activity of the electrode, improves the mass transfer efficiency of the electrolyte, reduces the internal resistance of the battery, and improves the structural stability of the electrode material after long-term circulation to a certain extent.
[0093] Application of the cellulose composite carbon aerogel prepared by the preparation method of the present invention in battery electrodes.
[0094] The present invention provides a cellulose composite carbon aerogel and a preparation method thereof, wherein cellulose nanofibers and carbon nanotubes are used as raw materials, and after dispersion mixing and dispersion, cellulose nanofibers / carbon nanotube composite carbon aerogels are prepared by bidirectional freezing, freeze drying, and high-temperature carbonization, namely, cellulose composite carbon aerogels. The present invention also provides the application of cellulose composite carbon aerogels in battery electrodes, which have an ultra-large specific surface area and excellent compression rate at ultra-low density, exhibit super-hydrophilicity and high electrochemical activity, good compression resilience, good structural stability, and certain mechanical strength, and can be used in various electrochemical-based water-based liquid flow batteries.
[0095] Compared with the prior art, in the present invention, (1) individual CNFs filaments are cross-linked within the layer. Although aerogels can be constructed, only part of the filaments between the layers play a supporting and connecting role, resulting in smaller pores in the aerogel and unclear boundaries between the layers. After adding CNTs, since CNTs and CNFs are not only cross-linked within the layer but also between the layers, CNTs play a supporting and connecting role, forming an aerogel with a honeycomb structure, making the pore structure more developed and less prone to collapse, and at the same time, the thermal degradation rate is lower. Under the same high-temperature carbonization conditions, its microstructure is more stable and the degree of graphitization is higher. Therefore, CNFs / CNTs is used as a carbon aerogel precursor, so that the CNFs / CNTs composite carbon aerogel has good structural stability and mechanical strength. (2) The honeycomb structure of CNFs / CNTs composite carbon aerogel enables it to effectively transmit compressive stress, withstand large compressive strain, and has good compressibility and elasticity; at the same time, the addition of CNTs significantly improves the structural stability of CNFs / CNTs composite carbon aerogel. The two work synergistically to improve the compressibility and elasticity of CNFs / CNTs composite carbon aerogel and ensure its mechanical strength. (3) The porous structure and high surface roughness of CNFs make CNFs / CNTs composite carbon aerogel have ultra-low density, super hydrophilicity and high electrochemical activity. The ultra-low density can reduce the weight of the liquid flow battery assembly design. The super hydrophilicity and high electrochemical activity can effectively reduce the resistance of electrolyte transmission during the operation of the liquid flow battery, improve the wettability, transmission rate and mass transfer uniformity of the electrolyte, thereby effectively reducing the polarization phenomenon and improving the utilization rate of the electrolyte. The present invention can be widely used in the field of battery technology.
[0096] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A method for preparing cellulose composite carbon aerogel, characterized in that: The following steps are involved: (1) preparing a suspension: mixing cellulose nanofibers, 2,2,6,6-tetramethylpiperidin-1-oxyl free radicals and sodium bromide in deionized water, stirring evenly, and adding sodium hydroxide to adjust the pH to about 10; adding sodium hypochlorite while stirring at room temperature, and continuously adding sodium hydroxide to keep the pH at about 10.5 until the pH value no longer decreases, and then adding ethanol to terminate the reaction; washing the product with deionized water until it is neutral, preparing a slurry, centrifuging, obtaining a cellulose nanofiber suspension, and refrigerating; (2) Mixing and dispersion: adding the refrigerated cellulose nanofiber suspension to the carbon nanotubes, vigorously stirring and ultrasonically dispersing to obtain a mixed solution, which is then refrigerated; (3) Bidirectional freezing: The mixed liquid is poured into a polytetrafluoroethylene mold. The bottom of the mold is connected to a copper column placed in liquid nitrogen. The temperature is transferred upward along the copper column, and the mixed liquid is gradually frozen. (4) Freeze drying: freeze drying the completely frozen mixed solution to obtain cellulose nanofiber / carbon nanotube composite aerogel; (5) High temperature carbonization: The cellulose nanofiber / carbon nanotube composite aerogel is subjected to high temperature pyrolysis to obtain a cellulose nanofiber / carbon nanotube composite carbon aerogel, namely, a cellulose composite carbon aerogel.
2. The method for preparing cellulose composite carbon aerogel according to claim 1, characterized in that: In step (1), the molar ratio of cellulose nanofibers, 2,2,6,6-tetramethylpiperidin-1-oxyl free radical, sodium bromide and sodium hypochlorite is 8-9:1:1:1-2.
3. The method for preparing cellulose composite carbon aerogel according to claim 1, characterized in that: In step (1), the concentration of the slurry is 2 mg / mL; and the slurry is refrigerated at 4°C.
4. The method for preparing cellulose composite carbon aerogel according to claim 1, characterized in that: In step (2), the mass ratio of cellulose nanofibers to carbon nanotubes is 1:0.5-2.
5. The method for preparing cellulose composite carbon aerogel according to claim 1, characterized in that: In step (2), the mixture is refrigerated at 4°C.
6. The method for preparing cellulose composite carbon aerogel according to claim 1, characterized in that: In step (3), the temperature of liquid nitrogen is -65--55°C, and the freezing time is 8-12h.
7. The method for preparing cellulose composite carbon aerogel according to claim 1, characterized in that: In step (4), freeze-dry at -60--50°C for 70-74h.
8. The method for preparing cellulose composite carbon aerogel according to claim 1, characterized in that: In step (5), pyrolysis is performed at 700-900°C for 0.5-2h.
9. A cellulose composite carbon aerogel prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the cellulose composite carbon aerogel prepared by the preparation method according to any one of claims 1 to 8 in battery electrodes.
Citation Information
Cited By
High-conductivity carbon aerogel as well as preparation method and application thereof
CN120398052A